Un ejemplo de explotación romana de yacimiento primario: la mina del rio de la Sierra (León) - García de Celis, Alipio; González Gutiérrez, Rosa Blanca; Luengo Ugidos, Miguel Ángel; Redondo Vega, José María (Estudios humanísticos. Geografía, historia y arte, 1995)
This article presents a geographical study of a roman gold-mine in the north-west of Iberian peninsula: the río de la Sierra mine. Several traces have been realized by ancient miners which already are present nowadays in our landscape. With these traces we can know a important part of that society like gold-mines and the hydraulic structure related with them.